Growth of magnesium diboride films on 2 inch diameter copper discs by hybrid physical–chemical vapor deposition. (16th February 2017) - Withanage, Wenura K; Xi, X X; Nassiri, Alireza; Lee, Namhoon; Wolak, Matthäus A; Tan, Teng; Welander, Paul B; Franzi, Matthew; Tantawi, Sami; Kustom, Robert L
Abstract: Magnesium diboride (MgB2 ) coating is a potential candidate to replace bulk niobium (Nb) for superconducting radio frequency cavities due to the appealing superconducting properties of MgB2 . MgB2 coating on copper may allow cavity operation near 20–25 K as a result of the high transition temperature ( T c ) of MgB2 and excellent thermal conductivity of Cu. We have grown MgB2 films on 2 inch diameter Cu discs by hybrid physical–chemical vapor deposition for radio frequency characterization. Structural and elemental analyses showed a uniform MgB2 coating on top of a Mg–Cu alloy layer with occasional intrusion of Mg–Cu alloy regions. High T c values of around 37 K and high critical current density ( J c ) on the order of 10 7 A cm −2 at zero field were observed. Radio frequency measurements at 11.4 GHz confirmed a high T c and showed a quality factor ( Q 0 ) much higher than for Cu and close to that of Nb.